Congenital prosopagnosia in a child: Neuropsychological assessment, eye movement recordings and training. Issue 3 (3rd April 2017) - Pizzamiglio, M. R.; De Luca, M.; Di Vita, A.; Palermo, L.; Tanzilli, A.; Dacquino, C.; Piccardi, L.
Abstract : Here we report the assessment and treatment of a 6-year-old boy (L.G.) who was referred to us for congenital prosopagnosia (CP). We investigated his performance using a test battery and eye movement recordings pre- and post-training. L.G. showed deficits in recognising relatives and learning new faces, and misrecognition of unfamiliar people. Eye movement recordings showed that L.G. focused on the lower part of stimuli in naming tasks based on familiar or unfamiliar incomplete or complete faces. The training focused on improving his ability to explore internal features of faces, to discriminate specific facial features of familiar and unfamiliar faces, and to provide his family with strategies to use in the future. At the end of the training programme L.G. no longer failed to recognise close and distant relatives and classmates and did not falsely recognise unknown people.